CAIPIRINHA-VIBE and GRAPPA-VIBE for Liver MRI at 1.5 T. Issue 2 (March 2015) - Morani, Ajaykumar C.; Vicens, Rafael A.; Wei, Wei; Gupta, Shiva; Vikram, Raghu; Balachandran, Aparna; Reed, Brandy J; Ma, Jingfei; Qayyum, Aliya; Szklaruk, Janio
<x xml:space="preserve">Abstract</x> Objective Three-dimensional T1-weighted (T1W) gradient recall echo volumetric interpolated breath-hold examination (VIBE) using generalized autocalibrating partially parallel acquisitions (GRAPPA) is one of the key sequences in liver magnetic resonance imaging (MRI) and is used for precontrast, dynamic postcontrast, and delayed postcontrast imaging. The purpose of this study is to compare image quality and liver lesion detection (LLD) on a shorter-duration T1W VIBE sequence using the controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA) technique with the conventional T1W GRAPPA-VIBE sequence during a single liver MRI session on a 1.5-T Seimens scanner. Methods Twenty consecutive patients (9 women and 11 men; age range, 36–85 years) were included in this prospective study. All patients underwent a complete liver MRI on a 1.5-T magnet (Aera; Siemens Medical Systems, Erlangen, Germany) that consisted of a T1W (in/out-of-phase), T2W, DWI, and precontrast and postcontrast multiphasic images (late arterial, 50 seconds, 120 seconds, and 300 seconds) with GRAPPA-VIBE. The CAIPI-VIBE images were acquired for precontrast and at 300 seconds (5 minutes) postcontrast phases (6.9 seconds per phase) in addition to GRAPPA-VIBE (21 seconds per phase). The shorter time for the CAIPI-VIBE was selected to allow postprocessing of image acquisition in the setting of multi–late arterial phase (single breath hold) postcontrast images. Five radiologists independently analyzed image quality with predefined scores for liver edge sharpness, artifacts, fat saturation deficiency, visualization of the portal veins and hepatic veins, and LLD (size, <0.5–3.8 cm). Score 0 was suboptimal (inadequate), 1 was acceptable for diagnosis, and 2 was optimal (excellent). Kappa statistics were used to assess agreement among readers. Generalized linear mixed model with generalized estimation equation method was used to estimate and compare the LLD failure rates. Results No statistically significant difference was seen in the degree of reader variability between CAIPI-VIBE and GRAPPA-VIBE for all evaluated categories using multirater κ statistics. For the precontrast and 5-minutepostcontrast phase sequences, greater than 95% of images were considered to be of acceptable quality in all image quality categories for both sequences. Forty-one lesions were evaluated in 17 patients with total of 204 observations (n = 204) by 5 readers. For 5-minute postcontrast images, the LLD rate of CAIPI-VIBE (80%) was lower than GRAPPA-VIBE (84%) (P = 0.03) for small lesions (0.5–1.7 cm). There was no significant difference in lesion detection on precontrast images. Conclusions At 1.5 T, the CAIPI-VIBE may be helpful in reducing scan time and demonstrates similar image quality compared with the traditional GRAPPA-VIBE. The CAIPI-VIBE has shorter breath-hold time requirement and thus can be an acceptable alternative for the precontrast and 5-minute postcontrast GRAPPA-VIBE in patients with breath-hold difficulties.